Meningitis retention syndrome - Abhishek Krishna; Pavan Devulapally; Ibrahim Ghobrial (Greater Baltimore Medical Center, 2012)
A 50-year-old Caucasian woman presented with signs and symptoms of meningitis preceded by a 3 day history of flu-like symptoms and progressive difficulty with urination. Cerebrospinal Fluid (CSF) analysis was consistent with aseptic meningitis. She was found to have a significant urinary retention secondary to atonic bladder. MRI of the brain and spine were normal and CSF-PCR (polymerase chain reaction) was positive for HSV-2. Urinary retention in the context of meningitis and CSF pleocytosis is known as Meningitis Retention Syndrome (MRS). MRS is a rare but important complication of meningitis most commonly associated with HSV-2. Involvement of central pathways may have a role in the pathogenesis of MRS but this is poorly documented. MRS is different from Elsberg syndrome wherein patients display features of lumbosacral polyradiculitis or radiculomyelitis. Early treatment with antiviral therapy was associated with a favorable outcome in our patient.